Pengembangan Teknologi Supercritical Geothermal: Potensi dan Strategi untuk Energi Bersih dan Berkelanjutan - Riska Laksmita Sari; Fauji Islami Phasya; Dian Pertiwi, Permata (Journal of Sustainable Energy Development, 2024)
Development of supercritical geothermal technology is a complex and challenging process that requires significant investment in research, technology development, and collaboration. However, the potential benefits of this technology include low carbon footprint, high efficiency, and the potential to provide reliable electricity, making it an important focus area for the future of clean energy production. This study is qualitative and uses literature study methods involving data collection and analysis from various literature sources, including scientific journals, books, and reports. The literature study was conducted by searching and collecting several relevant and accurate sources such as scientific journals, books, and official publications on the topic. Data collection was carried out by analyzing the content of each available source. The supercritical geothermal well drilling method can generate electricity of 3-5 MW per well. Several successful energy development projects include exploration well drilling in Mexico, Italy, Iceland, USA, Kenya, and Japan. Supercritical energy development technology is also continuously being developed, such as closed-loop and CO2 utilization. The development of supercritical geothermal technology is a complex and challenging process that requires significant investment in research, technology development, and collaboration. However, the potential benefits of this technology include low carbon footprint, high efficiency, and the potential to provide reliable electricity, making it an important focus area for the future of clean energy production.   Keywords: energy; geothermal; supercritical; technology; development; efficiency